2021
DOI: 10.1002/trc2.12120
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing transition to care homes for people with dementia in Northern Ireland

Abstract: Introduction The increasing number of people with dementia (PwD) is a significant health and financial challenge for countries. PwD often transition to a care home. This study explored factors predicting transition to care homes for PwD and the place and causes of death. Methods Data about dementia medication, care home transitions, demographic characteristics, deaths, and hospital admissions were extracted from national databases from 2010 to 2016. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
3
2
Order By: Relevance
“…This may indicate that people with a long time with dementia diagnosis, on average, experienced more severe symptoms entailing a need for care and support around-the-clock. Contrasting to our findings, German [ 33 ] and Irish [ 4 ] studies suggested that the care situation at home, including caregivers’ socioeconomic status, is more important for the transition to residential care than for how long time an individual has had a dementia diagnosis or severity of impairments. Higher age, female sex, and multiple comorbidities were also identified as significant risk factors for a transition to residential care of PlwD [ 4 , 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This may indicate that people with a long time with dementia diagnosis, on average, experienced more severe symptoms entailing a need for care and support around-the-clock. Contrasting to our findings, German [ 33 ] and Irish [ 4 ] studies suggested that the care situation at home, including caregivers’ socioeconomic status, is more important for the transition to residential care than for how long time an individual has had a dementia diagnosis or severity of impairments. Higher age, female sex, and multiple comorbidities were also identified as significant risk factors for a transition to residential care of PlwD [ 4 , 34 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrasting to our findings, German [ 33 ] and Irish [ 4 ] studies suggested that the care situation at home, including caregivers’ socioeconomic status, is more important for the transition to residential care than for how long time an individual has had a dementia diagnosis or severity of impairments. Higher age, female sex, and multiple comorbidities were also identified as significant risk factors for a transition to residential care of PlwD [ 4 , 34 ]. The fact that studies from different countries find different factors that are associated with moving to residential care, given a certain level of care needs, probably reflects the different systems for social care for older people, as well as differences in social policy in general, e.g., affecting the proportion of women in the labor market, which in turn affects their availability for informal care.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…20 Data for transitions to care homes were extracted through the Business Services Organisation and linked through HBS based on the General Practitioners’ claims for visiting patients in nursing or care home facilities. Similar to our work on transition to care homes for PwD, 21 care homes in this article refer to long-term care settings, residential care and nursing homes. The date of death was identified through data from death certificates from the General Register Office for people who were deceased between 2010 and 2016.…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature is somewhat inconclusive in terms of the changes between different types of use of eldercare among PlwD during the last years of life. Further, the existing literature is often inadequate in estimating of the length of stay in specific eldercare settings from diagnosis until death (Mjørud et al, 2020;Zafeiridi et al, 2021). Overall, previous research on dementia is fairly under-studied on what sociodemographic factors like age, sex, and cohabitation status affect eldercare services for PlwD.…”
Section: Eldercare and Dementiamentioning
confidence: 99%